The protective role of UMCA on bleomycin-induced lung fibrosis in rats - AYDEMİR, SEZGİN; ÖZKAN YENAL, NAZİYE; GÜÇLÜ, HÜLYA; YÜKSEL, MERAL; ÖZBEYLİ, DİLEK (My University, 2022)
Bleomycin (BLM), an antibiotic drug, is used for the treatment of cancers like Hodgkin’s lymphoma, Kaposi’s sarcoma and cervical cancer. The most common adverse effects occurred during BLM treatment is lung toxicity, which manifest as fibrosis. UMCA® (Pelargonium sidoides root extract) is a commercial product to treat acute and chronic upper respiratory tract infections. UMCA® has antiviral, antibacterial, immunomodulatory and cytoprotective properties, which is related to its polyphenol, coumarin, anthocyanidin and flavonoid contents. In the present study, we aimed to investigate the possible protective effects of UMCA® on BLM induced lung fibrosis in rats. Wistar albino rats was included in this study and randomly divided into 4 groups (Control, BLM, BLM+UMCA and UMCA). The control group received physiological saline. UMCA® was orally applied at a dose of 200 mg/kg/day and single intratracheal administration of BLM was conducted at a dose of 10 mg/kg. All animals were decapitated after 10 days and lung tissues was removed for the biochemical and histopathological examinations. Malondialdehyde (MDA) and glutathione (GSH) levels and Myeloperoxidase (MPO) activity were determined. Chemiluminescence (CL) method using luminol and lucigenin probes, additional nitric oxide and peroxynitrite measurements were applied. Histopathological observations were analyzed with H&E and Gomori's one-step trichrome staining. Collagen contents of lung tissue were also determined with a spectrophotometric method in paraffin-embedded tissues. BLM elevated MDA levels and MPO activity and depleted GSH levels in the lung tissues (p<0.001). CL measurement levels were also increased in BLM group respect to the control. Contrary to this, UMCA® treatment reversed these effects, significantly (p<0.001). BLM caused alveolar structural disturbance and inflammatory cell infiltrations and collagen content was also significantly increased in BLM group compared to the control (65.7±10.6, p<0.001). UMCA® administration reduced degenerations and decreased collagen content in the lung tissue. In conclusion, UMCA® has an antioxidant and protective effects on BLM induced lung fibrosis in rats.